The Role and Functions of Public Relations in Managing Social Conflicts Between Companies and Local Communities: A Case Study of PT Satria Bahana Sarana, Tanjung Enim, South Sumatra - Padri, Syahrul; Sakir, Icuk.M.; Santoso, Budi; Ardiansyah, Arief (Jurnal Indonesia Sosial Sains, 2026)
This study examines the role and function of Public Relations (Public Relations) in managing social conflicts between PT Satria Bahana Sarana (PT SBS) and local communities in Tanjung Enim, South Sumatra. Social conflicts between mining companies and the surrounding community are a phenomenon that often occurs due to differences in interests, misunderstandings of communication, and high expectations of the community. This research uses a constructivist-critical paradigm with a descriptive qualitative approach and case study methods. Data collection was carried out through in-depth interviews with eight informants, direct observation, and documentation. The analysis uses the theory of Conflict Management Styles from Thomas-Kilmann (in Wirawan, 2010) and is supported by the public relations theory of Cutlip, Center, and Broom (2006), symmetrical two-way communication of Grunig and Hunt (1984), and the theory of legitimacy of Suchman (1995). The results of the study show that conflicts that occur are generally situational with low intensity, triggered by miscommunication, differences in interests, high public expectations, and uneven distribution of information. PT SBS Public Relations applies five conflict management styles dynamically: accommodating, avoidant, collaborative, compromise, and competitive, which are adjusted to the characteristics and urgency of the conflict. Supporting factors for the implementation of the role of Public Relations include management support, clear SOPs, persuasive approaches, responsiveness, and sustainable CSR programs. Meanwhile, the inhibiting factors are slow decision-making due to organizational hierarchy, suboptimal internal coordination, and uneven distribution of information. This research emphasizes the importance of preventive communication, early public relations involvement, and strengthening the capacity of the public relations team to maintain a harmonious relationship between the company and the community.